Single set versus two sets of resistance training on muscular endurance, strength, fat percentages and blood pressure among recreationally trained men / Mohd Aizzat Adnan - Adnan, Mohd Aizzat (2013)
Several design program variables are very important in resistance training. Until now, the comparison of the effectiveness of one versus two sets or multiple sets of resistance training on trained population were still inconclusive. This study were conducted to compare the effects of one versus two sets resistance training on upper and lower body muscular strength, upper and lower body muscular endurance, body fat percentages and blood pressure among recreationally trained men. A total of 32 trained men were recruited in this study. They had been randomized into two groups (one set, n =16 or two set, n = 16) based on their body weight. The muscular strength were measured by bench press and squat using multiple-RM assessment. Muscular endurance had been measured by push up and 70% 1RM on leg extension while body fat percentages were measured using 8 -sites skinfolds measurement. Both groups engaged in six weeks of training. Significant improvement was noted throughout 6 weeks of training for both groups in all variables, (p<0.05), except for blood pressure (p>0.05). No significant differences between single set and two sets were found for all the variables (p>0.05) except for leg extension muscular endurance test between both groups, (p<0.05). In conclusion, single set had been found to produce similar effects as two sets on muscular strength, upper body muscular endurance, fat percentages and blood pressure among trained men.